1994
DOI: 10.1002/hep.1840190410
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of antibody to hepatitis E virus among Chinese subjects in Taiwan

Abstract: Recently, with an available serological hepatitis E virus diagnostic kit, the prevalence of IgG antibody to hepatitis E virus among Chinese subjects in Taiwan was evaluated by means of a solid-phase enzyme-linked immunoassay based on two recombinant hepatitis E virus antigens. The overall prevalence of hepatitis E virus antibody was 10.7% among 384 healthy subjects older than 20 yr but only 0.3% among 600 schoolchildren and young adolescents younger than 20 yr (p < 0.0001). Serial serum samples from 32 hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 14 publications
3
31
1
2
Order By: Relevance
“…A significant percentage (14.5%) of those patients had HEV infection. The prevalence seems to be higher than those reported from other studies of various populations in Taiwan, including 10.7% of healthy individuals (Lee et al, 1994), 8.8% of volunteer blood donor and college students (Peng et al, 1995), 3.4% of preschool children, and 12.5% of kindergarten teachers (Lin et al, 2004). As comparing with the report from Peng et al, their studied population is similar to ours by the geographic location (southern Taiwan) and age distribution.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…A significant percentage (14.5%) of those patients had HEV infection. The prevalence seems to be higher than those reported from other studies of various populations in Taiwan, including 10.7% of healthy individuals (Lee et al, 1994), 8.8% of volunteer blood donor and college students (Peng et al, 1995), 3.4% of preschool children, and 12.5% of kindergarten teachers (Lin et al, 2004). As comparing with the report from Peng et al, their studied population is similar to ours by the geographic location (southern Taiwan) and age distribution.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, our previous study showed that GB virus-C/hepatitis G virus infection more easily recovered in females than males (Cheng et al, 2000). Anti-HEV could persist 3-8 years after infection (Lee et al, 1994) and some decay later on. We, therefore, suspect the ability of females to recover faster than males from viral infections infers possible early decay of anti-HEV after infection.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…HEV-IgG may be cross-reactive or a false positive in patients with acute hepatitis A, B, or C, 11 and thus possibly in other viral diseases involving the liver, whereas HEV-IgM has been described to be falsely induced in patients with acute EBV or CMV infection. 12 Polyclonal stimulation of B-cells during EBV infection resulting in the production of low level HEV-IgM has been postulated.…”
Section: What Is Your Interpretation Of the Serological Results?mentioning
confidence: 98%